2006
DOI: 10.1088/1367-2630/8/9/214
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement controlled single-electron transmittivity

Abstract: We show that the electron transmittivity of single electrons propagating along a 1D wire in the presence of two magnetic impurities is affected by the entanglement between the impurity spins. For suitable values of the electron wave vector, there are two maximally entangled spin states which respectively make the wire completely transparent whatever the electron spin state, or strongly inhibits electron transmission.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(138 citation statements)
references
References 11 publications
4
134
0
Order By: Relevance
“…In Refs. [6,14] it was shown that, under such working conditions, the dynamics takes place as if the static particles all occupy the same site, i.e., …”
mentioning
confidence: 99%
“…In Refs. [6,14] it was shown that, under such working conditions, the dynamics takes place as if the static particles all occupy the same site, i.e., …”
mentioning
confidence: 99%
“…In this situation, the effective mass is 0.067 times the electron mass, and the strengths of interaction are J 1 = J 2 ≃ 1 eVÅas reported for magnetic impurities 11,19 . Figure 4 shows the transmission probability as a function of the electron energy if the distance between impurities is x 1 − x 2 = 1000Å.…”
Section: Two Delta-potential Systemmentioning
confidence: 69%
“…Thus, the study of electron scattering by impurities in quantum wires, using deltapotentials has been a subject of great interest in recent years 6,7,8,9 . In solid state quantum computation, finite δ-function potentials arrays are often used to describe an instantaneous interaction between flying qubits and statics qubits 10,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…This is the first step in a framework analogous to that in [13]. There the authors considered an isolated system in which an electron propagates in a one-dimensional wire interacting magnetically with two spin-1/2 impurities at x = 0 and at x = x 0 , and they analyzed the dependence of the electron's transmittivity on the impurities' states.…”
Section: Determination Of the Kossakowski Matrix Elementsmentioning
confidence: 99%
“…The zeroth order term in (13) vanishes because of the orthogonality of |ψ 3 to the spin states of the eigenstate |E , whereas the Hamiltonian term is always zero on the eigenstates, so we are left with…”
Section: Calculating the Transmission And Reflection Coefficients Formentioning
confidence: 99%